Global tuberculosis report 2017 / Autores Laura Anderson, Annabel Baddeley, Anna Dean, Hannah Monica Días, Dennis Falzob, Katherine Floyd, Inés García Baena, Nebiat Gebreselassie, Christopher Gilpin, Philippe Glaziou,Yohhei Hamada, Avinash Kanchar,Irwin Law, Christian Lienhardt, Andrew Soroka,Charalambos Sismanidis, Hazim Timimi, Wayne Van Gemert, Diana Weil y Matteo Zignol - Anderson, Laura; Baddeley, Annabel; Dean, Anna; Días, Hannah Monica; Falzob, Dennis; Floyd, Katherine; García Baena, Inés; Gebreselassie, Nebiat; Gilpin, Christopher; Glaziou, Philippe; Hamada, Yohhei; Kanchar, Avinash; et al. (France : World Health Organization, 2017)
The designations empoyed and the presentation of the material in this publication do no imply the expression of any opinion whatsoever on the part of WHO concerning the legal status of any country, territory, city or area or of its authorities, or concening the delimitation of its frontiers or boundaires
Contents Abbreviations Acknowledgements Executive Summary Chapter 1. Introduction Chapter 2. The sustainable development goals and the end TB startegy Chapter 3. TB disease burden Chapter 4. Diagnosis and treatment: TB, HIV-associated TB and drug-resistant TB Chapter 5. TB prevention services Chapter 6. Financing for TB prevention, diagnosis and treatment Chapter 7. Universal health coverage, social protection and social determinats Chapter 8. TB research and development Annexes 1. The WHO global TB database 2. Country profiles for 30 high TB burden countries 3. Regional and global profiles 4. TB burden estimates, notifications and treatment outcomes
Incluye Contenido
Keywords: TUBERCULOSIS; PULMONES -- ENFERMEDADES; TUBERCULOSIS PULMONAR; BACILO DE KOCH